Facing drug problems and advancing sentence plan. Prisoners’ perspectives on drug treatment programmes in Finland - Kaskela, Teemu (International journal of comparative and applied criminal justice, 2018)
In Nordic countries, the rapid development of various prison-based drug treatment (PDT) programmes emerged in the mid-1990s, and this development can be viewed as a criminological shift towards a “new form” of penal welfarism combining control and rehabilitation in a revised form in a new era. This article examines PDT programmes from the prisoners’ perspective to analyse their motives to participate, experiences, and relationships with counsellors, guards, and prisoners. Data were collected from interviews of the prisoners and observations in three Finnish prisons. Both the motives connected to handling drug problems and those connected to gaining an advantage for the duration of time spent in prison were experienced simultaneously by participants. Prisoners made a clear distinction between guards and drug counsellors and were somewhat confused by staff roles that combined both rehabilitative and control features. These findings suggest that new hybrid roles already found among correctional staff seem to exist also for prisoners.